Progress of the electricity sectors in South East Europe: Challenges and opportunities in achieving compliance with EU energy policy - Stefan Borozan (Elsevier, 2021)
This paper provides a comprehensive review of the current state and planned developments in the electricity sectors across eight countries in South East Europe (SEE). It highlights positive examples as well as barriers to efficient market operation and regional market integration. Progress is evaluated in terms of the level of implementation of required legislation, and the efficacy of regulatory frameworks to facilitate market integration of renewables, emerging technologies, and active demand participation. The observations are based on exhaustive research into European Union (EU) and national legislation, as well as a questionnaire taken by industry experts from the corresponding Transmission System Operators offering first-hand insights into the electricity sectors in the region. The conducted investigation demonstrates that SEE countries are at different stages in market opening and compliance with EU energy policy but show unity in the aim of integrating into the EU internal electricity market. The harmonization of legislation and technical requirements is highlighted as a precondition to this goal as it would facilitate cross-border trade, increase efficiency through the shared use of resources, and incentivize infrastructure investments. The analyses show that there is a continuous progress in development of wholesale and balancing markets in the region, but problems with liquidity and incumbents impede the process. The progress towards renewable generation targets varies between the countries, however, the region is committed to electricity sector decarbonization and digitalization in the future. Finally, the paper presents potential directions for regional power sector developments in response to the challenges in electricity market design for a low-carbon future.